Microbial Invasion vs. Tick Immune Regulation - Sonenshine, Daniel E.; Macaluso, Kevin R. (Frontiers in Cellular and Infection Microbiology, 2017)
Ticks acquire diverse pathogenic microbes while feeding on vertebrate blood. In response, the tick’s innate immune system activates an array of humoral factors and cellular processes to challenge and destroy these microbes. To evade these defenses, pathogens express surface ligands that bind to specific receptors on tick cells. Surviving microbes colonize tick tissues by different methods. Borrelia burgdorferi exploit bacteria-vector ligands to multiply, escape the midgut, enter the hemolymph, evade phagocytosis and invade salivary gland acini. Rickettsiae express outer membrane proteins that bind to receptors on tick cells, stimulating endocytosis and invasion. Infected cells initiate a signal cascade that rearranges the cell’s actin cytoskeleton and allows rickettsial multiplication by subverting cellular protective reactions and also spreads the infection. Ehrlichia and Anaplasma bacteria use caveolae-mediated endocytosis to invade cells and create membrane-bound intracellular compartments, providing a permissive environment wherein they multiply protected from host defense mechanisms. Babesia sp. also use novel methods to transit the midgut’s peritrophic barrier to invade epithelial cells, disable cell defenses, then develop and spread throughout the tick body. In this review, we summarize the current knowledge of how microbial pathogens invade and develop in their tick host, how the diverse components of the innate immune system are expressed to disable or destroy them and, finally, how some pathogens evade these defenses and multiply.